Assessment of cardiovascular risk in paediatric peritoneal dialysis patients: a Turkish Pediatric Peritoneal Dialysis Study Group (TUPEPD) report - ALPAY, HARİKA; YILDIZ, NURDAN (OXFORD UNIV PRESS, 2009)
Methods. We aimed to clarify arteriosclerotic risk and to document possible relationships between cardiovascular risk factors and echocardiographic parameters in paediatric peritoneal dialysis (PD) patients. M-mode/Doppler/tissue Doppler echocardiographic studies and lipid/lipoproteins, homocysteine, high-sensitivity C-reactive protein (HS-CRP) levels and carotid intima-media thickness (CIMT) were determined in 59 patients (age: 14.2 +/- 4.5 years) and in 36 healthy subjects. Results. Structural and functional cardiac abnormalities were observed in patients on maintenance dialysis. Increased left ventricular mass index (LVMI, P = 0.000), relative wall thickness (P = 0.000), myocardial performance index (MPI, P = 0.000) were documented in the patients. Lipoprotein (a) (P = 0.000), homocysteine (P = 0.001), HS-CRP (P = 0.000) and CIMT (P = 0.000) were significantly elevated in the patients. Left ventricular hypertrophy (LVH) was prevalent in 68% of the patients. Patients with LVH had higher levels of HS-CRP (P = 0.001) and CIMT (P = 0.028) than those without LVH. Haemoglobin was an independent predictor of LVMI (beta: -8.9, P = 0.001), while residual diuresis and CIMT were independent predictors of diastolic dysfunction (beta: -0.45, P = 0.034 and beta: 5.90, P = 0.008, respectively). Albumin (beta: -0.72, P = 0.018) and Kt/V urea (beta: -0.48, P = 0.012) were significant predictors of CIMT. There were positive correlations between LVMI and CIMT. HS-CRP was positively correlated with LVMI as well as CIMT. Conclusions. Elevated levels of atherosclerotic/inflammatory risk factors, low haemoglobin levels and loss of residual renal function and their negative effects on heart are of remarkable importance in paediatric patients on maintenance peritoneal dialysis. Achieving recommended targets for haemoglobin, blood pressure and Kt/V urea, preserving residual renal function as well as managing inflammation and subsequent arteriosclerosis is obviously essential to improve the patients' prognosis.
Keywords: cardiovascular disease; children; chronic kidney disease; echocardiography; peritoneal dialysis; LEFT-VENTRICULAR HYPERTROPHY; STAGE RENAL-DISEASE; C-REACTIVE PROTEIN; DIASTOLIC FUNCTION; YOUNG-ADULTS; VASCULAR CALCIFICATION; INFLAMMATORY MARKERS; CARDIAC-HYPERTROPHY; PRELOAD DEPENDENCE; ADIPONECTIN LEVELS